Pertimbangan Hakim Dalam Perkara Tindak Pidana Penggelapan Dana Kantor Cahaya Kerupuk Dihubungkan Dengan Kitab Undang-Undang Hukum Pidana - ananda siregar; Eka Juarsa, S.H., M.H. (UNISBA Press, 2023)
Determination of considerations for this case decision is a case decision given by the judge to Mr. Wendi Herdianto which has been regulated in Article 374 of the Criminal Code. The determination of this decision can be given to cases of criminal acts of embezzlement according to the rules. However, in implementing the consideration of the decision given by the judge to Mr. Wendi Herdianto, it is still not relevant to the case that occurred because the judge decided the case under article 374, but according to the author, the crime of embezzlement in accordance with this case is regulated in article 372 of the Criminal Code. This study explains that Mr. Wendi Herdianto received an irrelevant case decision, this is in accordance with what is regulated in Article 372 of the Criminal Code which is referred to as embezzlement in the main form. The article also contains that the criminal act of embezzlement committed is an act that is detrimental to the victim and the defendant has no legal or definite relationship with the injured party, in the sense that there is no working relationship that is bound to the defendants in that case. the defendant was not drafted a work appointment letter or work contract'' So it can be said that article 372 of the Criminal Code is more appropriate for imposing charges and punishments on the defendants compared to article 374 of the Criminal Code. In this case, the judge should do more revisions to the demands and sentences in the case above, so that it is more appropriate. This research uses a normative juridical approach to law (normative legal research method). The normative juridical research method is library law research which is carried out by examining library materials or mere secondary data. The results of this study indicate that the determination of the verdict on Mr. Wendi Herdianto in this case the article stated in the decision was not relevant, the judge was wrong in imposing the article on charges and sentences against the defendants, because the defendant was only a salesperson who did not have a contract/work tie with the company Penetapan pertimbangan putusan perkara ini merupakan putusan perkara yang diberikan oleh hakim kepada sdr Wendi Herdianto yang telah diatur dalam Pasal 374 KUHP. Penetapan putusan ini dapat diberikan kepada kasus tindak pidana penggelapan yang sesuai dalam aturannya. Akan tetapi dalam pelaksanaan penerapan pertimbangan putusan yang diberikan oleh hakim kepada sdr Wendi Herdianto ini masih kurang relevan dengan dengan kasus yang terjadi karena hakim memutus perkara dengan pasal 374 tetapi menurut penulis tindak pidana penggelapan yang sesuai dengan kasus tersebut diatur dalam pasal 372 KUHP. Dalam penelitian ini menjelaskan bahwa sdr Wendi Herdianto mendapatkan putusan perkara yang tidak relevan, hal ini sesuai dengan yang diatur dalam Pasal 372 KUHP ini disebut sebagai penggelapan dalam bentuk pokok. Dalam pasal tersebut juga berisi bahwa tindak pidana penggelapan yang dilakukan adalah tindakan yang merugikan pihak korban dan terdakwa tidak ada hubungan yang sah atau pasti dengan pihak yang dirugikan, dalam artian tidak adanya hubungan kerja yang terikat kepada para terdakwa pada kasus tersebut Sebagaimana disebutkan ‘’namun terdakwa tidak dibuatkan Surat pengangkatan kerja atau Kontrak Kerja’’ Sehingga dapat dikatakan pasal 372 KUHP lebih tepat untuk menjatuhkan tuntutan dan hukuman kepada para terdakwa dibandingkan dengan pasal 374 KUHP. Dalam ini hakim sebaiknya harus lebih melakukan revisi terhadap tuntutan dan penjatuhan hukuman terhadap kasus diatas, agar lebih tepat Penelitian ini menggunakan metode pendekatan hukum secara yuridis normatif (metode penelitian hukum normatif). Metode penelitian yuridis normatif adalah penelitian hukum kepustakaan yang dilakukan dengan cara meneliti bahan-bahan pustaka atau data sekunder belaka. Hasil dalam penelitian ini menunjukkan bahwa penetapan putusan kepada sdr Wendi Herdianto dalam kasus ini pasal yang tertera dalam putusannya belum relevan, hakim keliru dalam menjatuhkan pasal tuntutan dan hukuman terdahap para terdakwa, pasalnya terdakwa hanyalah seorang sales yang tidak memiliki kontrak/ikatan kerja dengan perusahaan